PERANCANGAN SARANA PENYAPU JALAN RAYA UNTUK KAWASAN PERKOTAAN: Manual Road Sweeper Machine - Roni H (Indonesian Society of Applied Science, 2014)
Development of the city in our country with all facilities and public facilities constructed within the framework of the modern era. However, the cleanliness of the city, especially the implementation of the highway is still impressive sweeping away from the modern age because of the cleanliness of the facility is still using a simple device. Although existing tools are more sophisticated street sweeper, but its use can not be sustained due to economic reasons and substantial operational costs. Through the design process, the design of the street sweeper means look for a solution that can ease the work of street sweeper. Designing started from existing products, street sweeper activity analysis and anthropometric measurements of components and users. Of this design obtained a draft means cheaper road sweeper and is expected to streamline and improve work efficiency street sweeper. Perkembangan kota di negara kita dengan segala fasilitas dan sarana umum dibangun dalam kerangka jaman modern. Namun, dalam penyelenggaraan kebersihan kota terutama penyapuan jalan raya masih berkesan jauh dari jaman modern karena fasilitas kebersihan ini masih menggunakan perangkat yang sederhana. Walaupun sudah ada perangkat penyapu jalan yang lebih canggih namun penggunaannya tidak dapat berkelanjutan karena alasan ekonomi dan biaya operasional yang cukup besar. Melalui proses desain, perancangan sarana penyapu jalan ini dicarikan solusi yang dapat meringankan pekerjaan penyapu jalan. Perancangan dimulai dari eksisting produk, analisis aktivitas penyapu jalan dan komponen serta pengukuran anthropometri pengguna. Dari perancangan ini didapatkan sebuah rancangan sarana penyapu jalan yang lebih murah dan diharapkan dapat mengefektifkan serta meningkatkan efisiensi pekerjaan penyapu jalan.